Unravelling human embryonic macrophage development using single cell sequencing and induced pluripotent stem cell models - Lee, Christopher Zhe Wei (Nanyang Technological University, 2023)
Macrophages are resident mononuclear phagocytes of the innate immune system whose primary functions include the phagocytosis and clearance of cellular debris, engulfment of pathogens and other foreign particulates, and regulation of inflammation. Of the myriad functions performed by macrophages, there has been increasing interest in and scrutiny of their role in the development and homeostasis of their host tissues, especially since embryonic macrophages have been observed to infiltrate their host tissues early on in organogenesis. Traditional dogma dictates that resident tissue macrophages (RTMs) develop from bone marrow hematopoietic stem cell (HSC)-derived monocytes. However through the use of fate mapping in mouse models, we now understand that embryonic macrophages from a non HSC-derived source seed the developing organs, and in some tissues persist independently of the circulating adult monocyte population under steady state conditions. Although the ontogeny of murine RTMs has since been clarified, it remained unclear whether this hematopoietic program is conserved in human development. Using scRNA-seq, we mapped the development of human embryonic macrophages, demonstrating their non-monocytic yolk sac origin and tracing their acquisition of tissue residency signatures in the head, liver, lung and skin. We compared early human yolk sac macrophage development to induced pluripotent stem cell-derived macrophage (iMac) development, and found remarkable transcriptomic similarity between the two, suggesting that these in vitro derived cells develop along the same developmental pathways as their in vivo counterparts and can be used as a surrogate to study human embryonic macrophage development.